Effect of public infrastructure investment on economic growth: study for the Puno Region, 2000 - 2019 - Quispe Mamani, Julio Cesar (2020)
The purpose of this research was to assess the inﬂuence of public infrastructure investment on the economic growth of the Puno region, for the period 2000-2019. The methodological design applied was non-experimental, with a longitudinal descriptive character and a quantitative approach, with data collection from the economic transparency portal of the Ministry of Economy and Finance (MEF). Time series were considered for the analysis of each of the variables, using the econometric model of maximum likelihood (MVS) LIN - LOG, these were used for a better comprehension of the role of investment in public infrastructure on economic growth. A clear relationship has been demonstrated between public infrastructure investments in the economic growth of the Puno region. Public infrastructure investment in education signiﬁcantly aﬀects economic growth, i.e. an increase of 1% in public infrastructure investment in education will increase the GDP by 3 054 862 soles. In the case of public infrastructure investment in health, it does not signiﬁcantly inﬂuence economic growth. Finally, public infrastructure investment in agriculture has a signiﬁcant inﬂuence, but indirectly, on economic growth. In other words, an increase in public infrastructure investment in agriculture of 1 percent would reduce GDPby 2 889 537 soles.